Employee’s skills to promote innovation in the enterprise – a perspective from the World Bank’s survey in Vietnam - Anh, Cao Thi Thu; Lien, Trinh Bich (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2021)
In the framework of the cooperation program between the Ministry of Science and Technology and the World Bank in Vietnam on innovation activities, the World Bank has surveyed a number of enterprises in Vietnam to assess the role of employee's skill to promote innovation. The survey was conducted in 5 provinces in 2019, the research was developed based on the methodologies used by the World Bank that adapted for Vietnam to explore: (i) the innovation skills and innovation activities in Vietnamese enterprises;and (ii) the innovation skills of the workforce in the enterprise. The survey results show that (i) There is a correlation between innovation activities and the skills of employees in the enterprise; (ii) A significant proportion of enterprises, especially innovative firms with medium skills and labor-intensive firms, do not undertake product and marketing innovation; (iii) Lack of innovation skills and limited financial access are two major obstacles that prevent enterprices innovative activities; (iv) Enterprises whose large proportion of employees have high literacy skills as well as the ability to "interact with others" and "manage emotions" are more likely to implement innovation; (v) There is a particularly close correlation between the skills of workers and the innovator in medium-skilled innovative enterprises; and (vi) The skills of managers and technicians have a special relationship with the innovation in the enterprise. Code: <span style="text-align: left; color: #000000; text-transform: none; text-indent: 0px; letter-spacing: normal; font-variant: normal; font-weight: 400; text-decoration: none; word-spacing: 0px; white-space: normal; orphans: 2; -webkit-text-stroke-width: 0px; background-color: #ffffff;">20091001